If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 12 = 2x + 72 Reorder the terms: 12 + 8x = 2x + 72 Reorder the terms: 12 + 8x = 72 + 2x Solving 12 + 8x = 72 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 8x + -2x = 72 + 2x + -2x Combine like terms: 8x + -2x = 6x 12 + 6x = 72 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 6x = 72 + 0 12 + 6x = 72 Add '-12' to each side of the equation. 12 + -12 + 6x = 72 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 72 + -12 6x = 72 + -12 Combine like terms: 72 + -12 = 60 6x = 60 Divide each side by '6'. x = 10 Simplifying x = 10
| 4x+40=8x+16 | | 5x+50=7x+10 | | 8x+27=5x+84 | | 7x+32=3x+100 | | 8x+72=2x+144 | | 4x+42=7x+6 | | 8x+72=2x+138 | | 12c-16d+8c= | | 9y-11+5y=25 | | 7x-14=4x+3 | | 5-4y+-1=-23 | | 0.065x=y-1.22 | | -9-3(2P-1)=-18 | | 19+h=-6-4j | | x^4+x^2+8=0 | | -6+5(8-k)-8k= | | 2x+7=5x-1 | | 12x^2+5x-28=0 | | 7k-2(3K+1)-9= | | x^2+x-90=0 | | 6(7+x)+5x= | | 10k-3k+5h= | | 4.5x^3+5x^2-12.5x=0 | | 8a-5a= | | 14-3(4n-1)= | | 4(6n+9)-10n= | | 3-11x=9+5x | | .66x+6=30 | | 5x-2=-8 | | -8n-8(-4-2n)= | | 5(x-1)-2x+2=35 | | 3(5+3x)-4x= |